Genetically Modified Food in Malaysia Halal Food Supply Chain: An Insight - Risyawati Mohamed Ismail; Mastora Mustafar (International Journal of Supply Chain Management, 2018)
The aim of this paper is to investigate Genetically Modfied Food(GMF) management and acceptance in the halal food supply chain and to explore how the GMF impacted Malaysia food consumerism. In this study, the researchers adopted in depth critical review of various publications and data made available on the issues and various studies on GMF consumerism and acceptance in Malaysia. The findings showed that in general GMF is still a new concept among Malaysians and despite a few studies on the matter, it is far from being able to conclude solidly or generalize compellingly the acceptance, understanding or even awareness among Malaysian consumers towards GMF. In the term of halal status of GMF, in depth and further study should be made on the unresolved issues concerning understanding on GMF products before any halal assessment could be done on it. Therefore, it is assumed that the subject of GMF in Malaysia is still far from being clear and much less distinctive among the consumers themselves. For future research, the researcher needs to take a look at the understanding level of GMF concept among consumers before wading down deeper on their behaviour, intention as well as awareness towards consuming GMF. Keywords: GMF, Halal, Food Supply Chain